VD_FINDINFO Décision / 2019 / 1007 vom 5. Dezember 2019 - VD Tribunal cantonal (2019)
RÉCUSATION, EXPERT, CONFLIT DE COMPÉTENCES, DÉCISION D'IRRECEVABILITÉ | 183 al. 3 CPP (CH), 56 CPP (CH), 60 CPP (CH)